SYSTEMATIC ANALYSIS OF INTEGRATED MARKETING COMMUNICATION RESEARCH - Reza Widhar Pahlevi; Narwanto Nurcahyo (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study aims to analyze international scientific articles for integrated marketing communication research systematically, both from the perspective of themes, research locations and subjects, as well as the research methods used. This study reviewed 149 scientific articles and presented four main findings. First. The first theme in marketing communications research is integrated with marketing communications and customer relationship management, the second theme deals with the concept known as value added of the plans developed for the role of communication. Second, the questionnaire is a data collection that is predominantly used. Third, research on integrated marketing communications, both in developing and developed countries, has almost the same number of studies. Fourth, based on the bibliometric technique using Vosviewer, it is divided into four clusters and recommends further research agendas to elaborate theoretical and methodological aspects by testing the four themes. By exploring these four themes, it will contribute further to the development of integrated marketing communications in the future.